Attitudes, motivation and achievement of Malaysian secondary school students towards learning English / David Owen Rock - David Owen , Rock (2021)
Success in second language learning (SLL) is of considerable importance in today’s highly interconnected world. However, the reasons behind success in SLL are still poorly understood. One promising line of research (Gardner 1985) proposes that differences in achievement result from differences in individual variables such as integrativeness, attitudes to the learning situation, motivation and language anxiety. However, despite its significance, this theoretical perspective has been much criticized in the literature, with the result that its status is currently uncertain. The objective of this research was therefore to test Gardner’s socio-educational model in the modern Malaysian context to evaluate its current utility. Structural equation modeling was used to investigate correlations between the stated variables among 278 upper secondary students in Malaysian National High Schools in the Klang Valley. Significant relationships were found between the model constructs investigated. It was concluded that despite the criticisms it has been subject to, the socio-educational model continues to offer a viable and useful perspective for investigations into the causes of success in SLL. The limitations of the research include the use of purposive rather than probabilistic sampling, the cross-sectional rather than longitudinal design of the research, and the fact that quantitative research, of its nature, is unable to offer deep insights into the reasons behind the findings. The significance of the research is first, that it suggests that researchers need not avoid the use of the socio-educational model where appropriate attention is paid to theoretical issues, measurement methods and analysis; and second, that there appears to be a place for the inclusion of cultural instruction modules in compulsory second language courses in high schools.